Causal effect of vitamin D on myasthenia gravis: a two-sample Mendelian randomization study - Fan, Yidan; Huang, Huaiying; Chen, Xiangda; Chen, Yuexuan; Zeng, Xiashi; Lin, Fenwei; Chen, Xu (Frontiers in Nutrition, 2023)
Introduction Observational studies suggest that vitamin D supplementation may be effective in preventing myasthenia gravis (MG). However, the causal relationship between circulating vitamin D levels and MG remains unclear. This study aimed to examine the genetic causality of circulating vitamin D and MG using data from large population-based genome-wide association studies (GWAS). Methods SNPs (single nucleotide polymorphisms) strongly associated with exposure were selected. Two-sample Mendelian Randomization (MR) was performed with inverse variance weighting (IVW), MR-Egger (Mendelian randomization-Egger), weight median and MR-PRESSO (Mendelian randomization pleiotropy residual sum and outlier) methods. Heterogeneity was tested via IVW and MR-Egger. Pleiotropy was tested using MR-Egger intercept test and MR-PRESSO method. MR-PRESSO was also used to detect outliers. Leave-one-out analysis was used to identify SNPs with potential effect. Reverse MR analysis was also performed. Result In IVW, circulating vitamin D levels had no causal effect on MG [OR = 0.91 (0.67-1.22), P = 0.532] and MG had no causal effect on circulating vitamin D [OR = 1.01(099-1.02), P = 0.663]. No heterogeneity or pleiotropy was observed (p > 0.05). Other MR methods also agreed with IVW results. Conclusion This study provides the causal relationship between genetically predicted circulating vitamin D levels and MG and provides new insights into the genetics of MG.